Choral speaking: perceptions and challenges in an ESL context / Evelyn Sharminnie Vasuthavan... [et al.] - Vasuthavan, Evelyn Sharminnie; Ranjethamoney Vijayarajoo, Angeline; Kumaran, Arutchelvi; Mohd Razali, Nur Hidayah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Choral Speaking is known for its' numerous benefits in the enhancement of the English Language in the ESL context. However, it has been found that both - learners and teachers alike, perceive Choral Speaking to be arduous. Hence, when performances and competitions are organised, there is a dual resistance and anxiety from the learners and teachers. This study looked at perceptions and challenges on Choral Speaking, of learners from a public university, and that of teachers from secondary schools in Malaysia. Methodology comprised qualitative and quantitative methods, where questionnaires and interviews were administered to the participants. Hence, data comprised responses from these two instruments. The findings showed that though the majority of the learners and teachers perceive Choral Speaking as beneficial, the challenges identified, caused reluctance in participation. This paper provides recommendations to address these issues.